A Dissertation Report on A Report Dynamic Reconnition System for Alphabetical Hand Gestures - ASEEMA SULTANA (2011)
INTERNAL GUIDE:RAJAPUSPHA T, MVJCE
Keywords: Report Dynamic Reconnition System for Alphabetical Hand Gestures